Organizational trust : a cultural perspective - Saunders, Mark, 1959- (New York : Cambridge University Press, 2010)
"The globalized nature of modern organizations presents new and intimidating challenges for effective relationship building. Organizations and their employees are increasingly being asked to manage unfamiliar relationships with unfamiliar parties. These relationships not only involve working across different national cultures, but also dealing with different organizational cultures, different professional cultures and even different internal constituencies. Managing such differences demands trust. This book brings together research findings on organizational trust-building across cultures. Established trust scholars from around the world consider the development and maintenance of trust between, for example, management consultants and their clients, senior international managers from different nationalities, different internal organizational groupings during times of change, international joint ventures, and service suppliers and the local communities they serve. These studies, set in a wide variety of national settings, are an important resource for academics, students and practitioners who wish to know more about the nature of cross-cultural trust-building in organizations"--Provided by publisher.
"Introduction To an ever-increasing extent, "work" involves close interaction and cooperation with people who come from a national-societal cultural background different from one's own. This emerging reality of work can be attributed to a number of factors. First, with the unrelenting advance of globalization, more and more organizations are taking a global approach to operations,"--Provided by publisher.
Machine generated contents note: List of figures; List of tables; Editors; Contributors; Editors' acknowledgements; Part I. The Conceptual Challenge of Researching Trust Across Different 'Cultural Spheres': 1. Introduction: unraveling the complexities of trust and culture Graham Dietz, Nicole Gillespie and Georgia Chao; 2. Trust differences across national-societal cultures: much to do or much ado about nothing? Donald L. Ferrin and Nicole Gillespie; 3. Towards a context-sensitive approach to researching trust in inter-organizational relationships Reinhard Bachmann; 4. Making sense of trust across cultural contexts Alex Wright and Ina Ehnert; Part II. Trust Across Different 'Cultural Spheres': Inter-Organizational Studies: 5. Examining the relationship between trust and culture in the consultant-client relationship Stephanos Avakian, Timothy Clark and Joanne Roberts; 6. Checking, not trusting: trust, distrust and cultural experience in the auditing profession Mark R. Dibben and Jacob M. Rose; 7. Trust barriers in cross-cultural negotiations: a social psychological analysis Roderick M. Kramer; 8. Trust development in German-Ukrainian business relationships: dealing with cultural differences in an uncertain institutional context Guido Mollering and Florian Stache; 9. Culture and trust in contractual relationships: a French-Lebanese cooperation Hela Yousfi; 10. Evolving institutions of trust: personalized and institutional bases of trust in Nigerian and Ghanaian food trading Fergus Lyon and Gina Porter; Part III. Trust Across Different 'Cultural Spheres': Intra-Organizational Studies: 11. The role of trust in international cooperation in crisis areas: a comparison of German and US-American NGO partnership strategies L. Ripley Smith and Ulrike Schwegler; 12. Antecedents of supervisor trust in collectivist cultures: evidence from Turkey and China S. Arzu Wasti and Hwee Hoon Tan; 13. Trust in turbulent times: organizational change and the consequences for intra-organizational trust Veronica Hope-Hailey, Elaine Farndale and Clare Kelliher; 14. The implications of language boundaries on the development of trust in international management teams Jane Kassis Henderson; 15. The dynamics of trust across cultures in family firms Isabelle Mari; Part IV. Conclusions and Ways Forward: 16. Conclusions and ways forward Mark N. K. Saunders, Denise Skinner and Roy J. Lewicki; Index.
Includes bibliographical references and index.
Keywords: Business ethics; Trust; Organization -- Psychological aspects